Building a Learning Community: Deep Learning Implementation at SMP Muhammadiyah 9 Surabaya - Amirul Fatah, Novi; Eriyanti, Ribut Wahyu; Sunaryo, Hari (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2026)
Education does not only function as a process of knowledge transfer, but also plays a role in shaping character, values, and 21st century skills. The implementation of deep learning requires a paradigm shift from teacher-centered learning to learner-centered learning. The success of deep learning implementation is greatly influenced by the role of schools as learning communities that involve all school members and stakeholders. This article aims to describe the good practices of SMP Muhammadiyah 9 Surabaya as a learning community in supporting deep learning based on the Merdeka Curriculum. This study uses a qualitative descriptive approach based on good practices carried out through On-the-Job Training (OJT) activities in the odd semester of the 2025/2026 academic year. The implementation stages include assess, design, implement, measure, and reflect. The results of the study show an increase in teacher collaboration through professional learning communities, increased student involvement in learning activities, and stronger partnerships between schools, parents, and the community. This program encourages the formation of a culture of reflection and continuous learning in the school environment. The findings of the study indicate that schools as learning communities are an effective strategy in supporting meaningful and sustainable deep learning.